The Genetic Consequences of Dispersal and Immigration in a Wild Great Tit Population - Andrea Estandía; Nilo Merino Recalde; Jon Slate; Ben C. Sheldon (Molecular Ecology, 2026)
Understanding how dispersal impacts the genetic makeup of populations is essential for predicting their responses to environmental change. Gene flow—via within‐population dispersal and external immigration—shapes population health and evolutionary potential by boosting genetic diversity, but it can also counteract local adaptation. We investigate these processes in a population of great tits ( Parus major ) in Wytham Woods, United Kingdom. This system represents a large, continuous population of a vagile, widely distributed species. Using a comprehensive social pedigree alongside two genomic datasets, one with 949 individuals genotyped at 600,000 SNPs and another with 2644 individuals typed at 10,000 SNPs, we demonstrate spatial genetic structure largely driven by the spatial and temporal clustering of close kin. We quantify how temporally persistent this pattern is and find that relatedness declines with geographic distance in a consistent manner across years, without a consistent genetic basis, a pattern which is frequently renewed due to high population turnover. Immigrants make up a substantial portion of the breeding population, yet are often assumed to be genetically distinct, unrelated and outbred—assumptions that can bias population inferences. We show that immigrants are indeed outbred, as are local birds; have fewer close relatives within the population, and are less likely to be related to their neighbours than locally born birds. Despite low F ST and no clear genome‐wide population structure, immigrants and locals can be distinguished above chance using a Random Forest classifier trained on SNP data. Our study highlights the complex interplay between dispersal, population turnover and spatial population structure, and suggests that great tits in Wytham Woods experience substantial gene flow within the population and from immigrants, maintaining high genetic diversity and reducing the possibility of local adaptation at this spatial scale.

Islands Promote Diversification of the Silvereye Species Complex: A Phylogenomic Analysis of a Great Speciator - Andrea Estandía; Nilo Merino Recalde; Ashley T. Sendell‐Price; Dominique A. Potvin; William Goulding; Bruce C. Robertson; Sonya Clegg (Molecular Ecology, 2025)
Geographic isolation plays a pivotal role in speciation by restricting gene flow between populations through distance or physical barriers. However, the speciation process is complex, influenced by the interplay between dispersal ability and geographic isolation, as seen in “great speciators” – bird species that simultaneously have broad island distributions but high levels of subspecific diversity. Comparing genomic population differentiation in species that occupy both continental and island settings can reveal the effects of different forms of geographic isolation and validate if the primary mechanism proposed to catalyse a great speciator pattern, that is, dispersal reduction following island colonisation, has occurred. The highly diverse white‐eye family Zosteropidae includes several great speciators, including the silvereye ( Zosterops lateralis ), with 16 subspecies (11 occurring on islands), distributed on the Australian continent and numerous southwest Pacific islands. We compared continental and island patterns of divergence using whole genome and morphological data. Australian mainland populations showed a low genetic population structure, lack of isolation by distance patterns and low morphological diagnosability, suggesting that the species' dispersal propensity in a continental setting is sufficient to overcome multiple forms of geographic barriers and large geographic distances. In contrast, except for island populations less than 200 years old, most island populations were highly genomically structured with clearer morphological diagnosability even if separated by relatively short geographic distances. The inferred reduction of dispersal propensity in island situations is consistent with the proposed model of great speciator formation on islands. Our phylogenomic analyses also allowed resolution of the silvereyes' evolutionary position, showing their relatively early emergence (~1.5 Mya) within the rapidly radiating Zosteropidae, while population‐level analyses demonstrated where morphological subspecies and genomic data align and disagree. However, the silvereye example also shows how uncertainties about relationships remain when reconstructing evolutionary history in rapidly radiating groups, even when whole genome data is available. Altogether, our results show how within‐species genomic and morphological patterns measured over broad spatial scales and with varying geographic contexts can help reveal when particular stages of speciation such as great speciators are likely to emerge.

A densely sampled and richly annotated acoustic data set from a wild bird population - Nilo Merino Recalde; Andrea Estandía; Loanne Pichot; Antoine Vansse; Ella F. Cole; Ben C. Sheldon (Animal Behaviour, 2024)